The COP9 signalosome coerces autophagy and the ubiquitin-proteasome system to police the heart - Liu, Jinbao (Autophagy, 2016)
We demonstrated for the first time that the COP9 signalosome (COPS) controls the degradation of a surrogate and a bona fide misfolded protein in the cytosol of cardiomyocytes likely via supporting ubiquitination by CUL/cullin-RING ligases, and that Cops8 hypomorphism exacerbates cardiac proteinopathy in mice, in which autophagic impairment appears to be in play. It will be extremely imprtant to investigate cardiac ablation of another Cops gene to decipher whether COPS8 deficiency phenotypes are attributable to the COPS or unique to COPS8.